THE “RIGHT” IN THE CHILEAN POPULAR FRONT: A STUDY OF “SEVERAL PERIODS”, 1932-1948. - Rubio Apiolaza, Pablo (Revista de Historia Social y de las Mentalidades, 2011)
Between 1938 and 1952, most of the Chilean governments implement policies put center- left. Greater political democracy and social rights, plus an economic strategy linked to the state-led industrialization seem to be the main areas of policy drivers of the period. However, in this scenario, the traditional right-composed of the Conservative and Liberal, became a protagonist who can not be underestimated. The hypothesis advanced is that the right in Chile is an active field and deep divisions, which prevented him from being a majority in Chile at that time. These hypotheses systematize and fall within a larger historical debate.